Smart farm mechanization Retrospective and prospective - Mehta, C R; Tiwari, P S; Chandel, N S (Indian Farming, 2021)
Smart technology in agriculture is an idea that refers to operating farms, utilizing modern sensors, controllers, actuators, along with information and communication technology (ICT) to enhance quantity and quality of crops. Smart farming involves not just individual machines but all farm operations. ICAR-CIAE, Bhopal has developed a web-based app that suggests machinery package based on agro-climatic region, state, district, cropping pattern and power source. App also provides an estimated cost of machinery package, list of manufacturers and their addresses. A smartphone based app ‘KRISHI Yantra Mitra’ is also available for selection of package of farm machinery to establish a custom hiring centre. Based on various inputs, a complete package of machinery is recommended by software for the selected region. Present Indian agriculture is highly labour intensive whereas smart agriculture is all about machines and technologies. Different types of sensors, instruments and machinery are being developed now-a-days for smart farming practices. A holistic, value-chain approach is necessary for smart agricultural mechanization, going beyond green production through precision agriculture and digital agriculture. There is a need of low cost, reliable and doable technologies suitable for small and marginal farmers to practice smart farming.